Highly microporous activated carbons derived from biocollagenic wastes of the leather industry as adsorbents of aromatic organic pollutants in water. Issue 3 (June 2017) - Lladó, J.; Gil, R.R.; Lao-Luque, C.; Solé-Sardans, M.; Fuente, E.; Ruiz, B.
Graphical abstract: Highlights: Valorisation of biocollagenic wastes from tanning industry. The activated carbons present specific surface area (SBET ) of up to 1664 m 2  g −1 . The adsorbents are mainly microporous with micropore volumes up to 0.536 cm 3  g −1 . Superior performance for adsorption of benzaldehyde (qmax : 3.77 mmol g −1 adsorbent). Acetanilide, aniline and benzoic acid were affected by nitrogen content on AC. Abstract: Leather industries generate large amounts of biocollagenic wastes that need to be processed. Moreover, the presence of aromatic organic pollutants produced by different industries (pharmaceutical, food, perfume, …) is increasing in surface and groundwater and this is seriously affecting the environment. The purpose of this study is to use biocollagenic wastes (shavings, trimmings and buffing dust) and their pyrolyzed products as bioprecursors of activated carbons for future waste water applications. Activated carbons were prepared by KOH and K2 CO3 chemical activation at different temperatures. The characteristics of the precursors and the influence of the activating temperature and activating agent on the process were studied and discussed. The obtained materials and two commercial activated carbons (WAC and YAO) were used as adsorbents to remove the following aromatic organic pollutants from the water: acetanilide, aniline, benzaldehyde, benzoic acid, methyl benzoate and phenol. The results obtained show that an increase in the activating temperature led to a higher textural development in the adsorbents. The best activated carbons were obtained by means of KOH chemical activation resulting in SBET and VTOT values of up to 1664 m 2  g −1 and 0.735 cm 3  g −1 respectively. All the adsorbents were predominantly microporous with a certain degree of mesoporosity and a significant amount of nitrogen (up to 3%). The main adsorption mechanism proposed for the different organic pollutants was dispersive interaction influenced by a hydrogen mechanism. Moreover, an increase in the nitrogen content of the adsorbents decreased the adsorption capacity of acetanilide, benzoic acid and aniline, whereas electrostatic influences reduced the adsorption capacity of benzoic acid.